"Enhanced, Edgier": A Euphemism for "Shame and Embarrassment"?. (6th May 2013) - Gostin, Lawrence O.
Abstract One of six commentaries on "Obesity: Chasing an Elusive Epidemic, " by Daniel Callahan, from the January‐February 2013 issue.